KERJASAMA PENGEMBANGAN PARIWISATA KEPULAUAN NIAS DENGAN REPUBLIK SEYCHELLES MELALUI NIAS STRATEGIC DEVELOPMENT PARTNERSHIP (NSDP) - Rezky Efryanto Zebua; Yusnarida Eka Nizmi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research will describes about Nias Strategic Development Partnership (NSDP). Nias Islands in North Sumatera well-known as “surfing dreamland” because some beaches in Nias Islands have perfect waves for surfing activity. This islands also perfect place for swimming, diving, or snorkeling. In other hand, this islands have unique culture and history such stones-jumping, megalith sites, and tradisional houses which have great potential as culture tourism. Unfortunetly, this tourism potential not managed professionally. Then, the local government of Nias Islands made a cooperation with Republic os Seychelles to help development tourism sector in Nias Islands. This research combining two methods between field research and library research to get all data and information. Field research excuted in Nias Island, especially in Gunung Sitoli City, South Nias Regency, and North Nias Regency. In other hand, library research collect some data and information from books, journals, and websites. This research use international cooperation theory and cultural diplomacy concept. The Government in entire Nias Islands promote their potential in tourism and culture to get attention of Republic of Seychelles. In other hand, the ambassador of Republic of Seychelles also offerring to help build the tourism sector in Nias Islands. The program of NSDP are focused to build tourism sector in Nias Islands such promote Nias Islands tourism and culture to the world, and build new resorst and hotels program. Beside that, NSDP also has another program such introduce Blue Economy and Responsible Fisheries to Nias Islands, build new eco-friendly energy resources, and agricultural program. Keywords: International Cooperation, Cultural Diplomacy, Tourism, Nias Islands, Nias Strategic Development Partnership (NDSP)